MACHINE LEARNING OPTIMIZATION IN THE FLOOD PRONE AREA MAPPING SYSTEM - Sitorus, Zulham; Hariyanto, Eko; Kurniawan, Fahmi (Proceeding International Conference of Science Technology and Social Humanities, 2022)
One of the areas in Batu Bara Regency, Pahlawan Village, Tanjung Tiram District, has an area of ​​173.79 km² and is located in a lowland area with an altitude of 0.-4.5m which is directly adjacent to the Malacca Strait to the east. Where almost half of the area is affected by sea tides, Hero Village has a tropical climate with two seasons namely the rainy season and the dry season. The people who live in Pahlawan Village, Tanjung Tiram District. There are so many obstacles faced by the people of Pahlawan Village, including the problem of flooding which has an impact on the health and the economy of the community. Lack of counseling and knowledge, as well as public awareness of the occurrence of flooding during high tides, and when the rainy season will increase the water discharge at sea level will rise so that it can cause flooding. Due to the occurrence of floods, and the impact of losses that affect material and non-material, it is very important to map flood-prone areas for regional development planning. Identification of potential floods involves machine learning using the Random Forest method, taking into account the factors that trigger floods. The Random Forest method also provides sensitivity parameters using the Receiver Operating Characteristic (ROC) curve which shows flood-prone areas such as Pahlawan Village, Tanjung Tiram District.